Traditional use of Achyrocline satureioides in coal mining areas - Dias Blanco, Graziela; Carvalho Schmidt, Estela; Lucia Campos, Mari; da Silva Galvan, Natiele; Hanazaki, Natalia (Ethnobotany Research and Applications, 2025)
Background: Mineral extraction areas are a significant environmental concern due to the contamination of soil, water, and plant resources. In these areas, some medicinal plant species have the potential to bioaccumulate trace elements. The medicinal species Achyrocline satureioides (Lam.) DC is a species that occurs naturally in roadsides and mining areas and has a bioaccumulating capacity. Given this situation, this study aimed to understand the traditional use of Achyrocline satureioides in coal-mined areas in southern Brazil and to analyze whether it occurs in areas contaminated by mining and potentially dangerous to the food security of local communities. Methods: We conducted 194 semi-structured interviews in the coal-mining region of Santa Catarina to understand where people collected the species, the frequency of consumption, and its associated traditional use. We also analyzed the soil in the collection areas to determine whether the areas were contaminated with trace elements from coal mining. Results: As a result, we found that the six collection areas for the species indicated by the interviewees had high concentrations of barium, cadmium, and lead. Among the interviewees, 81.4% of people reported consuming Achyrocline satureioides, with the highest consumption reported by women and older individuals. Conclusions: These results highlight the importance of investigating food safety in mined areas and its potential impacts on human health. Our studies have shown that human populations are consuming medicinal species with the potential to accumulate trace elements from areas contaminated by mining. Keywords: Ethnobotany, Ecotoxicology, Food safety, Mining Resumo Contexto: As áreas de extração mineral são uma preocupação ambiental significativa devido à contaminação do solo, água e recursos vegetais. Nessas áreas, algumas espécies de plantas medicinais apresentam potencial bioacumulador de elementos-traço. A espécie medicinal Achyrocline satureioides (Lam.) DC é uma espécie que ocorre naturalmente em beiras de estrada e áreas mineradas e apresenta capacidade bioacumuladora. Diante desta situação, o presente estudo teve como objetivo compreender o uso tradicional de Achyrocline satureioides em áreas mineradas para extração de carvão do sul do Brasil e analisar se ela ocorre em áreas contaminadas pela mineração e potencialmente perigosas para a segurança alimentar das comunidades locais. Metodologia: Foram realizadas 194 entrevistas semi-estruturadas na região carbonífera de Santa Catarina, para compreender onde as pessoas realizavam a coleta da espécie, frequência de consumo e o uso tradicional associado. Também realizamos a análise do solo das áreas de coleta para saber se as áreas apresentavam contaminação por elementos-traço oriundos da mineração de carvão. Resultados: Como resultado encontramos que as seis áreas de coleta da espécie indicadas pelos entrevistados apresentavam concentração elevada de bário, cádmio, chumbo, e níquel. Entre os entrevistados, 81,4% das pessoas afirmaram consumir Achyrocline satureioides, sendo que o maior consumo foi citado por mulheres e pessoas com idade maior. Conclusão: Estes resultados destacam a importância da investigação da segurança alimentar em áreas mineradas, e seus possíveis impactos para a saúde humana. Nossos estudos mostraram que as populações humanas estão consumindo espécies medicinais com potencial acumulador de elementos-traços de áreas contaminadas pela mineração. Palavras-chave: Etnobotânica, Ecotoxicologia, Segurança alimentar, Mineração